2017
DOI: 10.1111/crj.12650
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and factors associated with mortality in idiopathic pulmonary fibrosis: An experience from a tertiary care center in Pakistan

Abstract: Smoking, age greater than 60 years and hypoxemia were identified as factors that increased the odds of mortality in IPF patients, whereas pirfenidone was found to lower the odds of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Studies have reported that reduced pulmonary function, especially forced vital capacity (FVC), never smoking status, and baseline serum Krebs von den Lungen-6 (KL-6) are crucial risk factors that predict an AE of IPF [10,11,12,13]. Reduced FVC patients often have decreased normal lung area due to extensive fibrosis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Studies have reported that reduced pulmonary function, especially forced vital capacity (FVC), never smoking status, and baseline serum Krebs von den Lungen-6 (KL-6) are crucial risk factors that predict an AE of IPF [10,11,12,13]. Reduced FVC patients often have decreased normal lung area due to extensive fibrosis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The management of drug treatments of the severe COVID-19 patient is complex. The benefit/risk ratio of the pharmacologic agents used should be carefully monitored ( Zubairi et al, 2018 ; Ferrara, 2020 ). Appropriate use of medications may reduce the risk of severe COVID-19 complications and postinfection sequelae.…”
Section: Risk Factors Of Pulmonary Fibrotic/inflammatory State By Sars-cov-2mentioning
confidence: 99%
“…There have been reported that reduced pulmonary function especially forced vital capacity (FVC) ,never smoker and baseline serum Krebs von den Lungen-6 (KL-6) are crucial risk factors of AE of IPF [10][11][12][13]. Reduced FVC patients often have decreased normal area due to extensive fibrosis.…”
Section: Diagnosis Processmentioning
confidence: 99%